Improving Access to Justice: AI-Enabled Legal Assistance for Self-Represented Litigants - Ramprasad Reddy Mittana (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The integration of artificial intelligence into legal systems presents a transformative approach to addressing the persistent justice gap faced by self-represented litigants. This article examines how AI-enabled tools facilitate access to justice through automated document preparation, procedural guidance, and personalized legal information delivery. By analyzing existing implementation models alongside ethical and regulatory considerations, this article explores the technological foundations supporting these innovations while providing a framework for measuring their effectiveness. The discussion encompasses both current capabilities and potential future developments, offering a comprehensive assessment of how AI can empower individuals navigating complex legal processes without traditional representation while considering the necessary safeguards to ensure accuracy, accessibility, and appropriate boundaries between technological assistance and legal practice.